The Historical Criticism in The Women in the Castle by Jessica Shattuck - Salsabila, Arih (Journal of Literature, Linguistics, & Cultural Studies, 2023)
World War II occurred in Germany between 1933 and 1945, under the rule of Hitler and the Nazis, pitting Germany against the Allies. Propaganda played a significant role in their efforts to secure victory. Propaganda was employed to manipulate the perceptions and positions of various groups to align with the Nazis' agenda. This study focused on the forms of propaganda used by the Nazis against Non-Aryan groups, including Gypsies, Slavs, Jews, and Polish. It also explored how German society responded to this propaganda during the period of 1933-1945, as depicted in Jessica Shattuck's novel "The Women in the Castle." The research applied historical criticism, using the gray and black propaganda theories proposed by Seabury and Codevilla (1990). Additionally, the theories of gray and black propaganda by Garth S. Jowett & Victoria O'Donnell (2005) were used to support the research findings. The study felt under the category of literary criticism, gathering data from quotes, conversations, and narratives found in the novel "The Women in the Castle," published in 2017 by William Morrow. The research yielded three main results: First, it identified seven instances of gray propaganda and three instances of black propaganda. Second, it uncovered nine positive and seven negative responses to Nazi propaganda targeting Non-Aryan groups. Finally, the novel "The Women in the Castle" effectively reflected the actual socio-political conditions of Germany from 1933-1945, spanning from Hitler's rise to power as chancellor to World War II and the Holocaust, which involved various propaganda efforts to garner support from the populace. However, there were also those who resisted and acted as opposition.